Effect Of Different Types Of Banana Plants Fibres On The Physical, Mechanical And Thermal Properties Of Agar Based Composites - Muhamad Noor, Mohamad Ikhwan (Universiti Sains Malaysia, 2018)
In this work, three types of banana stem fibres which were from Pisang Awak, Pisang Nangka, and Pisang Emas were prepared with different compositions of agar that are 10%, 20%, 30% and 40% to form composite. The properties such as physical, mechanical, thermal, and surface morphology were characterized. Banana fiber and agar were grinded in order to produce the composite. These two components were mixed homogenously and evenly in order to get better distribution of the agar with the fibre. The composites were produced using hot press machine at temperature of 180℃ for 25 minutes. FTIR test was conducted on each types of banana fibres and agar which were in powder form to determine their functional group. Water absorption test was conducted using distilled water at room temperature. From the result, most of the composites showed the high value of water absorption as high content of agar increase. For mechanical testing, the tensile and impact strength were done to investigate the properties of the composite. Thermal properties of the composite also have been investigated by using by using Differential Scanning Calorimetry (DSC) to determine the melting temperature ( Tm ) and glass transition temperature ( Tg) meanwhile Thermogravimetric Analysis (TGA) was used to determine the decomposition pattern of the composite. As the content of agar increase to 40%, decomposition temperature increase except for Pisang Emas composite. The scanning electron microscope (SEM) was used to analyze the fracture morphology of the surface that was taken from impact test. From the SEM test, it can be observed that characteristic such as void, porosity and fibre pull out were presence on the fracture surface of the composite which give indication of the interaction between agar and fibre.